Inverted supernumerary tooth located in the hard palate: a littleknown story - Falcón-Guerrero, Britto Ebert (2024)
Supernumerary teeth are dental units that appear in addition to the regular number of teeth. Their most common location is at the level of the anterior midline of the maxilla, known as mesiodens, but they can also be paramedian; or in the position of a lateral incisor. This article reviews the case of an inverted permanent supernumerary mesiodens in a child aged 15 years and 3 months. The patient was non-syndromic and did not have any other supernumerary teeth in the permanent dentition. Using cone beam computed tomography (CBCT) of the region, we were able to assess the position, structure, and shape of the supernumerary, as well as establish an adequate treatment plan. The aim of this paper was to present this anomalous case of an inverted supernumerary tooth located in the palate, and to include a review of the literature on the few reported cases of this type.